The Western Australian border, where is it today? - Snow, Tony; Leighton, K.; Morgan, L.; Wheeler, K.; Plaiche, A. (Taylor & Francis Asia Pacific (Singapore), 2014)
In 1829 the Swan River Colony was established by Captain Stirling and England claimed the remaining western portion (New Holland) of the Australia continent up to the NSW border at 129° longitude. Eventually NSW was further reduced in area to create the State of South Australia (SA) and the Northern Territory (NT) that now share the common border with WA. It was not until 1921 that the two states of WA and SA agreed on a process to determine the accepted legal position of the Border. This agreement included the placing of two Cairns, the Kimberly Cairn and the Deacon Cairn, on the border at 129° longitude as determined from adjacent astronomical observations. These two cairns under the agreement now determine the physical location of the border today. In 2012, GPS surveys were carried out at both cairns to determine the accuracy of the two original surveys.